The influence of employee perceptions of training on turnover intention - Wong, M. (International Information Institute Ltd., 2016)
The objective of this study is to determine the impact of perceptions of training on turnover intention amongst employees of small and medium enterprises of manufacturing sector in Johor. Findings from this study demonstrated that employees who perceived that they have support from colleagues and supervisor tend to have lower turnover intention. This paper also discusses the implications for research and practice.